Rethinking labour migration: Covid-19, essential work, and systemic resilience - Anderson, B; Poeschel, F; Ruhs, M (Springer, 2021)
Many of the ‘essential workers’ during the Covid-19 pandemic are migrants, playing an important role for the continued functioning of basic services – notably health services, social care, and food supply chains. We argue that this role should be taken into account when assessing the impacts of migrant workers and in the design of labour migration and related public policies. Existing studies highlight how the employment of migrant workers in essential services is shaped by interests of employers, sectoral policies, and national institutions. Considerations of how migrants may affect the systemic resilience of essential services – in a pandemic or similar crises – are pervasively absent, not only in policy-making but also in research. Drawing on several disciplines, we outline the concept of systemic resilience and develop implications for the analysis and regulation of labour migration. We call for shifting the focus from the role of migrants in specific occupations and sectors in particular countries to transnational systems of production and service provision. To study how migrant workers affect systemic resilience, we propose an agenda for comparative research along three lines: comparing migrants to citizens within the same system, comparing migrants’ roles across systems, and comparing strategies for resilience adopted in different systems.